(3aJM GdbOhS aj TQM NWHI GdbGehSs - (3GdgdGdj , CHh GdYHGS CMeO Hf YHO GdYRjR Hf GdQTjO GdgdGdj GdSLdeGSj,J (B1175 (3g` s ((3MHjH Gddg Hf CMeO s)
(3ChdgG (B:s
(3bGd GdTjN HYO GdJjef HGdHSedI MSHeG JYGbO Ydjg Yed Cgd GdLfI GdMeO gh dZI GdhUa dCLd Lejd ENJjGQi s
(3BNQgG (B:s
(3hjCJi GdJhcd HeYfi GdJcad hefg MOjK Jhcd Gddg def NQL ai SHjdg EdN , Ci Jcad dg HPdc , ceG ai QhGjI CNQi hefg YO HYVge (B: (3MSHfG Gddg hfYe Gdhcjd GfJgi eG JjSQ ai TQM cdGe GdeDda s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI YJjbIs
(3fSNI eUMMI s
(3cJHJ HYV YHGQGJgG HGdMeQI s
(3MhGa GdChQGb eJbUaI s
Keywords: (3GddZIs